Ising model on the cayley tree with competing interactions up to the third nearest-neighbors with spins belonging to different branches of the tree - Ganikhodjaev, Nasir; Mohd Rodzhan, Mohd Hirzie (The Korean Physical Society, 2015)
We study the phase diagram of the Ising model on the cayley tree with competing interactions up to the third nearest-neighbors with spins belonging to different branches of the tree. In addition to the expected ferromagnetic and paramagnetic phases, we present a new paramodulated phase. Morover, the transition lines are analyzed and they are in agreement with the lines obtained numerically. Lastly, the stability of the anti-ferromagnetic phase was studied in detail by investigating the Lyapunov exponent associated with the corresponding dynamical system.